Langzeitergebnis nach Ballonangioplastie kruraler Arterien: Welche Faktoren beeinflussen die Beinerhaltungs- und Überlebensraten? = Long-term results after balloon angioplasty of crural arteries : Which factors influence leg salvage and survival rates? - Tesdal, Inge Kaare; Krzemien, Christian Klaus; Weiß, Christel (Der Radiologe, 2016)
Aim: Clinical and statistical study analysing factors with influence on success rates, procedure-related complications, and long-term results for patients who underwent angioplasty of the crural arteries. Material and methods: Retrospectively we evaluated all patients who underwent angioplasty of the crural arteries due to critical chronic limb ischemia or severe claudication in the time period from 1/2002 to 12/2005. These patients were contacted in the time period from 1/2009 to 12/2010, and a follow-up examination including angiography was performed or telephone interviews were conducted with patients, relatives and referring physicians for follow-up. 212 patients with a mean age of 77.8 years (99 women and 113 men) underwent crural angioplasty on 239 limbs. The primary end points were the limb salvage rate and patient survival rate. The secondary end points included the complication rate, technical success rate, and patency rate. The prognostic relevance of treatment and selected variables with respect to limb salvage and patient survival were analysed with multiple logistic regression. Results: The technical success rate was 98.4%. Between 1/2009 and 12/2010, 49.5% of the patients died. An angiographic follow-up study was performed in 49.9% of the treated legs. The primary patency-rate (72% after 6 months and 62.8% after 12 months) was significant, influenced only by the riskfactor dialysis (p = 0.0207). After a mean follow-up of 3.7 years, 48 patients (22.6%) experienced minor- or major-amputation on 53 legs (22.2%). The limb salvage rate (Kaplan-Maier estimation) was 85.4% after 5 years. The mean survival rate according to Kaplan-Meier was 79.7, 72.2, 67.3 and 51.4% after 1, 2, 3 and 5 years, respectively. Results of multiple logistic regression analysis showed that negative prognostic variables with respect to patient survival were amputation (p = 0.0017) and dialysis (p = 0.0011) and with respect to limb salvage dialysis (p < 0.0001) and non-patent peroneal artery (p < 0.0001). Conclusion: Balloon angioplasty of the crural arteries shows a high technical success rate with an acceptable complication rate. Dialysis and non-patent peroneal artery are negative prognostic variables for the clinical long-term success.
Gesehen am 27.03.2019